Biodigestion of cassava peels blended with pig dung for methane generation - Oparaku, N. F.; Ofomatah, A. C; Okoroigwe, E. C. (African Journal of Pig Farming, 2013)
Biogas production from cassava (Manihot esculentus) peels and pig dung under a mesophilic temperature condition was investigated. Three blends of the wastes and a control labeled as B1, B2, B3 and C representing blend 1 (50:50 peel/dung), blend 2 (30:70 peel/dung), blend 3 (10:90 peel/dung) and control (pig dung alone) were used, respectively. Biodigestion of the wastes blends and control was carried out simultaneously under the same environmental and operational conditions of 30 days retention period using four metallic biodigesters of 32 L capacity each. The biogas yield result shows that blend 2 yielded the highest cumulative biogas of 78.5 L, while the least yield of 61.7 L was obtained by blend 3. When compared with the control set up and biodigestion of cassava waste alone from literature, there was blending effect resulting in increase in yield of biogas over the sole digestion of cassava peel or pig dung. Methane production leading to the combustibility of the biogas started at 6th , 5 th, 5th and 4th days for B1, B2, B3 and C, respectively. This, in agreement with earlier studies show that better handling of cassava peels for energy production would be achieved by blending it with animal wastes in the right proportion.